Gangguan Fungsi Hati pada Pasien Abses Hati Amebadengan Lama Perawatan di Rumah Sakit Atmajaya - Novia, Jessica; Cahyadi, Alius (Majalah Kedokteran Indonesia, 2018)
Introduction : Amoebic liver abscess is a manifestation of extra-intestinal amoebiasis which is caused by Entamoeba histolytica infection. Patients with amoebic liver abscess usually have elevated liver function test results that will prolong the hospital stay.The aim of this study is to correlate liver dysfunctions and duration of hospital stay inamoebic liver abscess patients. Methods : This was a correlative analytic cross-sectional study. The participants of this study were patients diagnosed with amoebic liver abscess in Atma Jaya Hospital from January 2014 to December 2017. The length of stay and the liver function test result swere observed and analyzedusing Spearman correlation test. Results : There were 16 patients diagnosed as amoebic liver abscess, which 15 of them were male, with average age of 44.56 years old. The average length of stay was 10 days. Enlarged liver was found in 87.5% of the patients. The average AST, ALT, Alkaline phosphatase, and gamma-GT were 34 U/L, 60.63 U/L, 184.82 U/L, and 176.17 U/L respectively. The liver function test results and length of stay had neither normal distribution nor significant correlationusing Spearman correlation test. Conclusion : There is no significant correlation between liver function test results and length of hospital stay in patients with amoebic liver abscess.